A European circular single market for economic security and competitiveness - Heather Grabbe; Luca Léry Moffat (Bruegel, 2024)
If the European Union is to achieve a sustainable net-zero economy, resources need to be used much more efficiently. Extraction from nature and processing of materials are the principal causes of biodiversity loss and are also major sources of pollution, water stress and greenhouse gas emissions. Resources are used inefficiently currently because market and government failures create a nexus of disincentives and barriers to firms and individuals, hindering them in making resource-efficient choices. The most prominent failure is the artificial cheapness of raw materials because the environmental and human costs of extraction are not including in their prices. A powerful way to improve resource efficiency is to increase circularity, so that fewer resources are used to meet the same level of human need. This can be done by extending the duration of use and reuse of materials, and by reducing resource demand from the start by designing products and systems for optimal efficiency. A circular single market would allow faster de-risking from toxic dependencies and economic coercion by authoritarian regimes. It would increase resilience in the context of fragile supply chains while reducing instability from volatile commodity prices. Firm competitiveness would also be enhanced, given that European companies operate on a continent that is poor in energy and natural resources, and are thus very exposed to future scarcity of resources when climate impacts will make water and land scarcer. If firms were to optimise production and consumption systems for efficiency now, they would be ahead of the curve. To develop the circular economy further, the EU will need to spur investment. Public policy that sets common standards and a predictable regulatory framework would accelerate the development of markets for inputs such as recyclates and services such as repair, both in the EU and in trade partners. The EU has established a legislative framework for the circular economy but it needs scaling up in the forthcoming Circular Economy Act.
Keywords: 330; climate change; competition policy